Pengukuran Tingkat Kematangan Tata Kelola Teknologi Informasi Pada Dinas Komunikasi dan Informatika Kabupaten Lamongan Menggunakan Framework COBIT 4.1 Domain Plan and Organise (PO) dan Acquire and Implement (AI) - Moch. Fadel Satrio; Suprapto Suprapto; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Dinas Komunikasi dan Informatika Kabupaten Lamongan is regional equipment organization (OPD) which is have scope in communication and informatics with responsibility for providing services to the community for transparent and accountable governance. Along with the use of information technology that is increasing by government institutions, Good IT Governance is required in accordance with Peraturan Menteri Komunikasi dan Informatika Republik Indonesia Nomor 41 Tahun 2007. Based on the results of interviews, the implementation is still not optimal with standard operational procedure (SOP) that are not yet available. Beside that, the maintenance of system/application is doesn't planned. Therefore, the purpose of research to knowing maturity level of IT Governance in the institution using COBIT 4.1. The domains used are Plan and Organise (PO) and Acquire and Implement (AI). Based on the results of research obtained an average value maturity level of each domain. PO domain have value 1,52 and AI domain have value 1,42. To increase the value, so given recommendation can be applied institution. Some recommendations are make document of strategic IT Plan, set procedure, tools and technique about development of information system architecture standardized.